1998
DOI: 10.1038/34862
|View full text |Cite
|
Sign up to set email alerts
|

Geological evidence for solid-state convection in Europa's ice shell

Abstract: The ice-rich surface of the jovian satellite Europa is sparsely cratered, suggesting that this moon might be geologically active today. Moreover, models of the satellite's interior indicate that tidal interactions with Jupiter might produce enough heat to maintain a subsurface liquid water layer. But the mechanisms of interior heat loss and resurfacing are currently unclear, as is the question of whether Europa has (or had at one time) a liquid water ocean. Here we report on the morphology and geological inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
284
2
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(301 citation statements)
references
References 17 publications
13
284
2
2
Order By: Relevance
“…Recent studies have revealed that low viscosities due to small grain sizes are required for convective instability in ice shells. Convection can start in an ice shell above an internal ocean if the ice grain size is less than a few milli meters for medium and large sized icy satellites such as Europa, Ganymede, and Callisto (Pappalardo et al, 1998;McKinnon, 1999;Barr et al, 2004;Barr and Pappalardo, 2005;McKinnon, 2006) and if the ice grain size is less than a few hundred microns for the smaller icy satellite Enceladus (Barr and McKinnon, 2007a). Our preliminary results suggest that such small grain sizes are achieved and kept constant by the presence of very small fractions of insoluble dust particles.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Recent studies have revealed that low viscosities due to small grain sizes are required for convective instability in ice shells. Convection can start in an ice shell above an internal ocean if the ice grain size is less than a few milli meters for medium and large sized icy satellites such as Europa, Ganymede, and Callisto (Pappalardo et al, 1998;McKinnon, 1999;Barr et al, 2004;Barr and Pappalardo, 2005;McKinnon, 2006) and if the ice grain size is less than a few hundred microns for the smaller icy satellite Enceladus (Barr and McKinnon, 2007a). Our preliminary results suggest that such small grain sizes are achieved and kept constant by the presence of very small fractions of insoluble dust particles.…”
Section: Resultsmentioning
confidence: 77%
“…Because the ice viscosity in the grain size sensitive creep regime strongly depends on grain size, many stud ies have examined the critical grain size required for con vective instability in ice shells above internal oceans for various icy satellites (Pappalardo et al, 1998;McKinnon, 1999;Barr et al, 2004;Barr and Pappalardo, 2005;McK innon, 2006;Barr and McKinnon, 2007a). In a convection current, grain size is controlled by several kinetic process es such as grain growth, dynamic recrystallization, and high pressure transformation (Karato, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The combination of geological, compositional, gravity, and induced magnetic field measurements all indicate a contemporary global saline liquid water ocean of ~100 km in depth (Anderson et al, 1998;Pappalardo et al, 1998;Kivelson et al, 2000;Zimmer et al, 2000;Hand & Chyba, 2007). Cycling of the ocean with a silicate seafloor and oxidant laden surface ice could yield an ocean rich with the elements and chemical energy needed to sustain life (Chyba 2000;Chyba & Hand, 2001;Hand et al, 2007;Hand et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Remote observations of the jovian satellite Europa indicate that a liquid water ocean may lie beneath its solid ice surface [Khurana et al, 1998;Cart et al, 1998;Pappalardo et al, 1998]. Furthermore, the ocean appears to be underlain by a differentiated, rocky interior [Anderson et al, 1998].…”
Section: Introductionmentioning
confidence: 99%